Imunossupressão na paracoccidioidomicose murina: envolvimento das células supressoras mieloides (MDSCs) na imunidade dos hospedeiros. - Preite, Nycolas Willian [UNIFESP] (2023)
Previous studies in paracoccidioidomycosis (PCM), the most prevalent systemic mycosis in Latin America, revealed that the immunity of hosts is strongly regulated by several suppressive mechanisms mediated by tolerogenic plasmacytoid dendritic cells, by the enzyme indoleamine 2,3-dioxygenase (IDO-1) and by regulatory T cells (Treg). IDO-1 has also been seen to orchestrate local and systemic immunosuppressive effects through the recruitment and activation of myeloid-derived suppressor cells (MDSCs), a heterogeneous population of myeloid cells with a potent ability to suppress T cell responses. These cells regulate immune responses and tissue repair in healthy individuals and rapidly expand during infection. However, the involvement of MDSC during PCM was never investigated. The presence, phenotype, and immunosuppressive mechanisms of MDSCs were evaluated at 96 hours, 2 and 8 weeks of infection in C57BL/6 mice. In addition, disease severity and various characteristics of the immune response were evaluated in MDSC-depleted or non-MDSC-depleted mice using three different in vivo treatment strategies: antibody against Gr1+ cells, LXR receptor agonists, and the chemotherapeutic agent 5-fluorouracil (5-FU). We observed that both monocytic MDSCs (M-MDSCs) and polymorphonuclear MDSCs (PMN-MDSCs) massively infiltrate the lungs during P. brasiliensis infection. We were also able to demonstrate that the partial reduction of MDSC promoted treatments with 5-FU or anti-Gr1 resulted in more prominent Th1/Th17 lymphocyte responses. This more robust immune response resulted in a regressive disease with reduced fungal burden on target organs and decreased lung pathology when compared to a control group. On the other hand, treatment by LXR receptor agonists wasn't able to deplete MDSCs during PCM. MDSC suppressive activity on CD4 and CD8 lymphocytes, as well as on Th1/Th17 cells, has also been demonstrated in vitro in co-culture experiments. In contrast, adoptive transfer of MDSCs to mice infected with P. brasiliensis resulted in more severe disease. Together, our data show that MDSC abundance in the PCM was linked to more severe disease and was associated with weakened Th1 and Th17 protective immune responses. However, the protective cellular immune response could be rescued by treatments mediated by partial or total depletion of MDSCs, which resulted in less severe disease and controlled tissue pathology. Thus, MDSCs emerge as a potential target cell for adjuvant therapy of PCM.